Ultrasound Evaluation of Therapeutic Response to Tofacitinib and Upadacitinib in Patients with Rheumatoid Arthritis—Real-Life Clinical Data - Vladimira Boyadzhieva; Konstantin Tachkov; Soner Emin; Zhaklin Apostolova; Rumen Stoilov; Guenka Petrova; Nikolay Stoilov (Biomedicines)
Background: In recent years, musculoskeletal ultrasonography (MSUS) has established itself as a reliable method for evaluating disease activity in combination with clinical examination and laboratory tests. Objectives: In this pilot study, we aimed to evaluate the ultrasound response to treatment with tofacitinib and upadacitinib on tendons and joints in comparison to clinical and laboratory results in patients with RA who have shown inadequate response to conventional synthetic and/or biologic disease-modifying antirheumatic drugs (cs/b DMARDs). Methods: This study presents the MSUS assessment of therapeutic response in RA patients treated with tofacitinib or upadacitinib over a 24-week period. In a prospective, single-center study, patients were treated with upadacitinib 15 mg/daily or tofacitinib 2 × 5 mg/daily or 11 mg/daily, in combination with or without methotrexate or another conventional DMARDs. Disease activity was assessed by DAS28-CRP, CDAI, and SDAI, as well as MSUS. Patients were evaluated at baseline for ultrasound measures and at weeks 2, 4, 8, 12, and 24 for the rest of the indicators. For each patient, we used two ultrasound (US) scores (gray-scale, GS, and power Doppler, PD scores) and the system of European Alliance of Associations for Rheumatology outcome measures in rheumatology (EULAR-OMERACT) US scoring (combined GS and PD). We also calculated the tenosynovitis score (GS and PD) according to OMERACT recommendations. Results: A total of 53 patients were recruited. A total of 25 patients with a mean age of 56 ± 11.6 SD were followed in the upadacitinib group, and 22 patients with a mean age of 56.9 ± 11.3 were followed in the tofacitinib group. At baseline, DAS28-CRP for the upadacitinib group was 5.57 ± 1.24, and for tofacitinib, it was 4.77 ± 1.47. The baseline visit (GS, PD, and combined—US) and tendon US scores (GS and PD) were, respectively, 23 ± 2.96, 15 ± 2.56, 24.08 ± 3.36, 11.04 ± 2.21, and 8.44 ± 1.65 for the upadacitinib group. USGS-J—23 ± 3.55, USPD-J—13.36 ± 2.44, OMERACT composite—23.4 ± 3.84, USGS-T—12.18 ± 2.23, and USPD-T—9.5 ± 1.92 were found in the patients treated with tofacitinib. In both groups of patients, a significant reduction was found in both DAS28-CRP and the described MSUS scores at weeks 8, 12, and 24 (p < 0.05). Conclusions: Upadacitinib managed to produce lower echography scores much faster than tofacitinib; however, the differences in effectiveness evened out at weeks 12 and 24, with all patients being adequately controlled.